Optimization of operation mode of static thyristor compensators of reactive power while their supply with voltage of polygonal form by the criterion of the minimum of specific consumed active power - Hrytsiuk, Yu. V.; Pietukhov M. V., M. V.; Rohalskyi, B. S.; Svyrydov, M. P. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Operating modes of three-phase static thyristor compensator of reactive power with an earthed neutral are considered while their supply with voltage of polygonal form. The approach , the essence of which involves the use of filter compensating device usually applied for compensation of higher harmonics, for formation of polygonal voltage is offered. As optimization criterion the minimum of specific consumed active power is used. Economic efficiency of functioning static thyristor compensator is proved in case of its voltage supply of rectangular and sawtooth form as compared with basic variant ( sine wave voltage supply).